2021
DOI: 10.1088/1742-6596/2017/1/012010
|View full text |Cite
|
Sign up to set email alerts
|

Feature extraction Hue, Saturation, Value (HSV) and Gray Level Cooccurrence Matrix (GLCM) for identification of woven fabric motifs in South Central Timor Regency

Abstract: South Central Timor (TTS) is one of the districts that has a weaving culture and also produces woven cloth in East Nusa Tenggara. The many types of woven fabric from each TTS tribe makes outsiders and even native TTS people do not recognize the typical TTS woven fabric, therefore we need a system that can help facilitate the community in recognizing the type and motif of woven fabric. In this study, digital image processing is used to identify the type of woven fabric in the TTS district using the HSV color fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 3 publications
0
4
0
1
Order By: Relevance
“…Research was carried out to identify types of woven fabrics in TTS district using the HSV color feature extraction method, and GLCM texture characteristics, and to measure the similarity of woven fabrics using the Euclidean distance metho. The results obtained in this research obtained a GLCM texture accuracy level for color features of 55%, HSV color features of 62.5% and combination of color and texture features of 91.67% [10].…”
Section: Introductionmentioning
confidence: 67%
“…Research was carried out to identify types of woven fabrics in TTS district using the HSV color feature extraction method, and GLCM texture characteristics, and to measure the similarity of woven fabrics using the Euclidean distance metho. The results obtained in this research obtained a GLCM texture accuracy level for color features of 55%, HSV color features of 62.5% and combination of color and texture features of 91.67% [10].…”
Section: Introductionmentioning
confidence: 67%
“…So, after obtaining the HSV matrix, the process carried out is quantizing the color histogram. This process is carried out to improve performance and reduce the computational burden of calculating image pixels [16]. A simple equation to get the HSV value is as follows:…”
Section: ) Geometric Invariant Moment: Geometric Invariantmentioning
confidence: 99%
“…Furthermore, from the integration of the GLCM feature extraction method and geometric feature extraction of a region of interest (ROI) for classifying tuna, it was found that the best classification accuracy was 86.76% obtained through the GLCM method [15]. In addition, the use of the HSV color feature extraction method and GLCM texture feature extraction to identify the type of woven fabric shows that the accuracy of the color and texture combination features is 91.67% [16]. Siar and Teshnehlab [17] used a combination of feature extraction to categorize tumor disease from digital images using the CNN method; the results obtained were very accurate, namely 99.7%, and increased when compared to using only one feature extraction method.…”
Section: Introductionmentioning
confidence: 99%
“…Agar dapat mempermudah dalam pengolahan citra, umumnya citra dengan ruang warna RGB akan diubah terlebih dahulu pada ruang warna Hue, Saturation dan Value atau HSV. Model warna HSV memberikan gambaran mengenai pewarnaan yang sama dengan intuisi manusia dalam menangkap warna [22]. Proses mengubah citra RGB menjadi citra HSV berguna untuk memudahkan proses segmentasi karena pada proses ini akan menghasilkan citra dengan warna HSV yang terlihat pada objek yang akan dilakukan segmentasi.…”
Section: Transformasi Citra Rgb Ke Hsvunclassified